Decomposition and nutrient release from leaf litter of trees in pastures - Bruno-Eutimio, Delia Ivette; Avendaño- Yáñez, María de la Luz; Perroni, Yareni; Salinas-Ruíz, Josafhat; Vargas- Mendoza, Mónica de la Cruz; López-Ortíz, Silvia (Ecosistemas y Recursos Agropecuarios, 2022)
Scattered trees in pastures are an important source of nutrients recycled through leaf litter released annually. The objective was to assess the decomposition and nutrient release by leaf litter from Vachellia pennatula and Lysiloma acapulcense in a sub-humid warm climate. Decomposition litterbags were set under the canopies and then collected, and soil humidity and temperature were measured over a 32-week period. A randomized block design was used, and litter decomposition was modeled in four treatments: litter from L. acapulcense under shade from L. acapulcense (1), litter from V. pennatula under shade from L. acapulcense (2), litter from L. acapulcense under shade from V. pennatula (3), and litter from V. pennatula under shade from V. pennatula (4). Chemical composition of leaf litter was assessed. Chemical composition of leaf litter was assessed. Chemical composition variables evaluated (C/N ratio, lignin, cellulose, and hemicellulose) were good predictors of decomposition. Remnant leaf litter at 32 weeks was similar in all treatments (P = 0.999). The decomposition rate (k) ranged from -0.00090 to -0.00096 across treatments, showing a low decomposition rate (t50 = 1.98-2.11 yr, t99 = 13.2-14.0 yr), where only litter fragmentation took place during the 32-week period, across decomposition conditions. Nitrogen and at the end of the study suggesting nutrient sequestration by microorganisms (e.g. fungi and bacteria) associated with the litter during the study period. Litter decomposition and nutrient release from these tree species which have a high C/N ratio are relatively slow under sub-humid warm climate conditions.